Peran Fisioterapi dalam Meningkatkan Kemandirian Lansia melalui Penilaian Mobilitas Fungsional Menggunakan Timed Up and Go Test - Catherine Hermawan Salim; Astrid Komala Dewi; Paramita Boni Lestari; Wirya Limala Putra; Luthvya Ramadhani; Harris Rizky Fajar Abadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The increasing elderly population presents challenges in healthcare services, particularly related to decreased mobility and independence in daily activities. Physiotherapy plays a crucial role in maintaining and improving the mobility function of older adults through appropriate evaluation and intervention approaches. One simple, valid, and reliable measurement tool for assessing functional mobility is the Timed Up and Go Test (TUG). This study aims to examine the role of physiotherapy in increasing independence in older adults through functional mobility assessment using the TUG. The method used was a descriptive-analytical study with a cross-sectional approach in a group of older adults. Measurements were conducted using the TUG to assess mobility, balance, and fall risk. The assessment results were then used as the basis for planning physiotherapy interventions, which included muscle strength training, balance training, and functional exercises. The results showed that older adults with better TUG scores had higher levels of independence in daily activities. Targeted physiotherapy interventions based on TUG results have proven effective in improving mobility and reducing fall risk. Therefore, using the TUG as an initial assessment tool is crucial in determining appropriate rehabilitation strategies. In conclusion, physiotherapy plays a significant role in increasing the independence of older adults through an approach based on functional mobility assessment using the TUG. Routine implementation of this assessment is expected to support optimal quality of life for older adults.